Beyond databases, architectures and structures : 11th International Conference, BDAS 2015, Ustron, Poland, May 26-29, 2015, Proceedings - Kozielski, Stanisław; Mrozek, Dariusz; Kasprowski, Paweł; Małysiak-Mrozek, Bożena; Kostrzewa, Daniel (Communications in Computer and Information Science, 2015)
This book constitutes the refereed proceedings of the 11th International Conference entitled Beyond Databases, Architectures and Structures, BDAS 2015, held in Ustroń, Poland, in May 2015. This book consists of 53 carefully revised selected papers that are assigned to 8 thematic groups: database architectures and performance; data integration, storage and data warehousing; ontologies and semantic web; artificial intelligence, data mining and knowledge discovery; image analysis and multimedia mining; spatial data analysis; database systems development; application of database systems.